2004
DOI: 10.4049/jimmunol.173.4.2607
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bovine Homologues of Granulysin and NK-lysin

Abstract: Granulysin and NK-lysin are antimicrobial proteins found in the granules of human and swine cytotoxic lymphocytes. A murine counterpart to granulysin has not been identified to date, indicating the importance of additional models to fully characterize the role of granulysin-like molecules in the immune response to infectious disease. Two partial nucleotide sequences corresponding to the complete functional domain of granulysin and NK-lysin were amplified from bovine PBMC mRNA. Following stimulation with phorbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 30 publications
6
88
2
Order By: Relevance
“…Compared with the classical antimicrobial peptides, NK-lysin and granulysin are much larger with 78 and 74 amino acid residues and a globular three-dimensional structure. Since the initial identification of NK-lysin in porcine and granulysin in humans a few years ago, a bovine homolog was recently identified (Endsley et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the classical antimicrobial peptides, NK-lysin and granulysin are much larger with 78 and 74 amino acid residues and a globular three-dimensional structure. Since the initial identification of NK-lysin in porcine and granulysin in humans a few years ago, a bovine homolog was recently identified (Endsley et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although a bovine homolog has recently been identified [13], the status of the NK-lysin/granulysin antimicrobial class in lower vertebrates is unknown. As part of a larger effort to characterize the catfish innate immune system, we report here identification, molecular cloning and characterization, and expression of a NK-lysin gene from channel catfish (Ictalurus punctatus).…”
Section: Cmentioning
confidence: 99%
“…The circulatory population then rapidly expands and shows an activated profile with increased CD25 + expression. The cells have been shown to be cytotoxic [34] and express perforin [35] and granulysin [22]. Contact dependant interactions between DC and WC1 + γδ cells have demonstrated that DC induce activation of WC1 + γδ cells which leads to IFN-γ release [36].…”
Section: Immunity Against M Bovis Infection In Cattlementioning
confidence: 99%
“…The primary cell type performing this function is the CD8 + T cell. Also, other cells which have this cytolytic capacity include NK cells, CD4 + T cells, and γδ T cells [22,29].…”
Section: Immunity Against M Bovis Infection In Cattlementioning
confidence: 99%
See 1 more Smart Citation